أساليب تمويل مشاريع القطاع الصناعي بالإعتماد على محفظة التمويل البنكية الإسلامية - برحومة, عبد الحميد; عزوز, منير (Université de M'sila, 2016)
The multiplicity and complexity of the activities of industrial enterprises with the emergence of the need for new financing formulas accompany this evolution with the emergence the so-called Islamic financing formulas, Which formed a diverse funding portfolio, It concerned with providing all production processes requirements And transactions associated with it. Which include those related to the cycle of exploitation (short-term) or related to investments (longterm) Under the terms of that is balanced in achieving the goals between the parties to the financing process within the provisions of the Islamic Sharia. But this type of funding is still facing many challenges, which must reduce the risks to gain the confidence of investors and this can be achieved only through the sensitization of financial institutions and industrial customers of the importance of this funding and the positive results arising from its use.
Keywords: Funding, Islamic finance portfolio, the industrial sector.